Children with disabilities in Malaysia and their educational rights - Othman, M. F.; Rahmat, N. E.; Abdul Aziz, N.; Abdul Hak, N.; Kamarudin, D. (Human Resource Management Academic Research Society, 2022)
Education is essential to everyone, including children with disabilities, since it makes them better citizens and ensures a bright future. The United Nations has recognised the right to education through a number of declarations and treaties. However, in Malaysia, even though children with disabilities are promised to be given educational rights on an equal basis as other normal children, it is still in the grey area due to the non-existence of specific Act relating to special education for children with disabilities. Not to mention, children with disabilities are considered as burden to their families and always being neglected due to their disabilities. These problems can be reduced if their educational rights are protected effectively. Hence, a legal framework of special education for children with disabilities is needed to protect their educational rights. This research adopts a doctrinal or library-based research methodology by examining legal statutes for example the Federal Constitution of Malaysia, the Persons with Disabilities Act 2008, the Education Act 1996 and its regulations, textbooks and journal articles relating to special education for children with disabilities in Malaysia. The purpose is to investigate whether the laws that we have in Malaysia are sufficient to protect the educational rights of children with disabilities. It is found that the educational rights of children with disabilities in Malaysia are not fully protected due to uncertainty in laws, lack of human capital and lack of facilities in the Special Education sector. The current laws that are relating to special education for children with disabilities in Malaysia are too general and lack of punishment provisions which allow someone to violates the laws. Hence, children with disabilities cannot enjoy their educational rights on an equal basis as other normal children. This paper will be beneficial to the Malaysian government, specifically the Ministry of Education and the Ministry of Women, Family and Community Development, in enhancing the protection of the educational rights of children with disabilities in Malaysia. Besides, the children with disabilities themselves, their parents, and society will benefit from this research through the recommendations given to protect children with disabilities' educational rights effectively. It is proposed for future research to compare the law and practice relating to special education in other jurisdictions to see the differences in the implementation in the Special Education sector.